2022
DOI: 10.15252/embj.2022111485
|View full text |Cite
|
Sign up to set email alerts
|

Microglial TNFα orchestrates protein phosphorylation in the cortex during the sleep period and controls homeostatic sleep

Abstract: Sleep intensity is adjusted by the length of previous awake time, and under tight homeostatic control by protein phosphorylation. Here, we establish microglia as a new cellular component of the sleep homeostasis circuit. Using quantitative phosphoproteomics of the mouse frontal cortex, we demonstrate that microgliaspecific deletion of TNFa perturbs thousands of phosphorylation sites during the sleep period. Substrates of microglial TNFa comprise sleep-related kinases such as MAPKs and MARKs, and numerous synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 116 publications
0
13
0
Order By: Relevance
“…We demonstrated that there is an interaction between brain-resident macrophages and VS, which leads us to expect that brain-resident macrophages are also involved in regulating sleep. While there is a limited number of studies examining the regulatory role of microglia in VS 12, 23, 35 , a comprehensive understanding of this regulation, as well as the specific parameters of the VS affected by brain-resident macrophages, remains unclear. To address this, we depleted microglia from the brains of mice for two weeks using colony-stimulating factor 1 receptor (CSF1R) inhibition via PLX5622 36 and allowed them to repopulate for four weeks (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that there is an interaction between brain-resident macrophages and VS, which leads us to expect that brain-resident macrophages are also involved in regulating sleep. While there is a limited number of studies examining the regulatory role of microglia in VS 12, 23, 35 , a comprehensive understanding of this regulation, as well as the specific parameters of the VS affected by brain-resident macrophages, remains unclear. To address this, we depleted microglia from the brains of mice for two weeks using colony-stimulating factor 1 receptor (CSF1R) inhibition via PLX5622 36 and allowed them to repopulate for four weeks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, investigating the separate contributions of microglia and CAMs in sleep regulation using Cre lines under the promoter of Hexb 63 and Mrc1 64 genes, respectively, would be a starting point. The observed VS phenotypes may also be influenced by disruptions in other central factors (such as protein phosphorylation orchestrated by microglial TNF-α) 12 and peripheral players (CSF1R inhibition also effects circulating and tissue macrophages) 65 warranting further investigations. Overall, our results shed new light on the complex interaction between the neuroimmune system and sleep regulation, and it paves the way for future investigations in this field.…”
Section: Discussionmentioning
confidence: 99%
“…was observed. 45 Thus, it appears that PLPPR3 S351 is a functionally relevant site, and it would be worth testing its function in the context of sleep.…”
Section: Plppr3 Is a Synaptic Protein Phosphorylated By Pka At S351mentioning
confidence: 99%
“…Recent studies have highlighted the integral role of microglia in the regulation of neuronal activity and synaptic plasticity, such as learning and memory, 38,39 sleep, [40][41][42] anxiety-like behaviors, 10 compulsive behaviors, 43 alcohol intake, 44 pain, 45 and seizures. 46 Beyond direct physical interactions with neurons, these studies suggest alternative regulatory mechanisms whereby microglia release soluble factors and phagocytose extracellular matrix (ECM) to modulate neuronal activity.…”
Section: Microglial Gi Signaling As a Potential Target For Neuromodul...mentioning
confidence: 99%